Ranking the Suppliers using a Combined SWARA-FVIKOR Approach - Mehdi Ajalli; Mohammad Mahdi Mozaffari; Rohollah Salahshori (International Journal of Supply Chain Management, 2019)
People are evaluating suppliers due to their responsibility which requires the need of a structured process for supplier evaluation. In this paper we used a new model for weighting of criterias and ranking the alternatives. This model is the combination of SWARA (Stepwise weight assessment ratio analysis) and FVIKOR (VlseKriter ijumskaOptimizacija I KompromisnoResenje) methods which evaluate the main criterias based on evaluation of factors that have major impacts on quality of suppliers, and selects the best suppliers according to the criterias. SWARA method is used in determining the weights of the criteria by decision makers and then rankings of the suppliers were determined by Fuzzy VIKOR method. The proposed method in this study is used for ranking the three suppliers of ABZARSAZI in Iran by five indexes that have major impacts on it. For this purpose, in this paper, designed questionnaires are sent to 20 professional experts in different departments of ABZARSAZI COMPANY in Iran for evaluating the criterias using SWARA. The result showed that Delivery is the most important criterias. Such, the results of FVIKOR technique showed that supplier 1 is the best supplier. This proposed approach gives an evaluation method for all of the companies in order to help managers to identify the best suppliers.